Harmonization of Bordetella pertussis Real-Time PCR Diagnostics in the United States in 2012 - Williams, Margaret M. (J Clin Microbiol, 2014)
Real-time PCR (rt-PCR) is an important diagnostic tool for the identification of Bordetella pertussis, Bordetella holmesii, and Bordetella parapertussis. Most U.S. public health laboratories (USPHLs) target IS481, present in 218 to 238 copies in the B. pertussis genome and 32 to 65 copies in B. holmesii. The CDC developed a multitarget PCR assay to differentiate B. pertussis, B. holmesii, and B. parapertussis and provided protocols and training to 19 USPHLs. The 2012 performance exercise (PE) assessed the capability of USPHLs to detect these three Bordetella species in clinical samples. Laboratories were recruited by the Wisconsin State Proficiency Testing program through the Association of Public Health Laboratories, in partnership with the CDC. Spring and fall PE panels contained 12 samples each of viable Bordetella and non-Bordetella species in saline. Fifty and 53 USPHLs participated in the spring and fall PEs, respectively, using a variety of nucleic acid extraction methods, PCR platforms, and assays. Ninety-six percent and 94% of laboratories targeted IS481 in spring and fall, respectively, in either singleplex or multiplex assays. In spring and fall, respectively, 72% and 79% of USPHLs differentiated B. pertussis and B. holmesii and 68% and 72% identified B. parapertussis. IS481 cycle threshold (C(T)) values for B. pertussis samples had coefficients of variation (CV) ranging from 10% to 28%. Of the USPHLs that differentiated B. pertussis and B. holmesii, sensitivity was 96% and specificity was 95% for the combined panels. The 2012 PE demonstrated increased harmonization of rt-PCR Bordetella diagnostic protocols in USPHLs compared to that of the previous survey.